Development and commercialization of the awajún traditional ceramic, district Santa Maria de Nieva, province Condorcanqui, Amazonas region, period 2019-2021 (SCIÉNDO INGENIUM, 2022)
The objective of this study was to determine the measure of elaborating and commercializing the traditional Awajún ceramic art of the District of Santa María de Nieva located in the Department of Amazonas, year 2019-2021, constructive cultural partner of each Awajún native community, which in total belongs to each ceramic woman who transmitted the occupations of each father to his son, working in each small family workshop, which was not formalized as a company, limiting each option to successfully achieve commercialization. The method used is quantitative, since it was based on each quantifiable data; presents a non-experimental design, due to the fact that each phenomenon was observed naturally in its environment; The type of research was descriptive since this method has as its characteristic the description and interpretation of a systematic set of facts, where it allows searching for the analysis through the collection of each informative data, as well as individually measuring each variable and the measures were reported. calculated; the technique used was the survey and observation guide. The most important conclusion was that by applying an adequate process of developing and seeking improvement in the markets internally and externally in traditional Awajún ceramic art, it will help to improve the living conditions of each Awajún female potter.
Keywords: Elaboration; Commercialization; Traditional Ceramic